Development of an evaluation strategy of hydronic balancing valves for radiant floor heating systems. (July 2015) - Rhee, KN; Shin, MS; Yeo, Myoung-Souk; Kim, KW
In order to increase thermal comfort and energy efficiency, individual room control is highly recommended for radiant floor heating systems. For this reason, hydronic balancing is essential to provide the design flow rate to each branch circuit, which can be regarded as the ultimate goal of individual room control for radiant floor heating systems. In general, balancing valves are widely applied to hydronic circuits of radiant floor heating systems in common residential buildings, in order to achieve the purpose of hydronic balancing. This study aims to suggest an evaluation strategy of balancing valve performance for radiant floor heating systems. In the strategy, adjustment range and accuracy are evaluated by using the Kv value, in order to evaluate the balancing performance for practical applications of balancing valves. Additionally, the flow distribution by balancing valves was evaluated with the hydronic network simulation, by which flow quotients of hydronic circuits were investigated. Based on the evaluation strategy, the performances of six different balancing valves, which are applied to typical residential buildings, were successfully evaluated. Practical application : This study presents an evaluation strategy to evaluate the performance of hydronic balancing valves for radiant floor heating systems. The proposed evaluation strategy will be able to provide a method to analyse the impact of hydronic balancing and to determine suitable balancing valves for radiant floor heating systems in residential buildings. Therefore, it is expected that the results will be helpful to researchers for indoor environment, building service engineers, system designers, and those who want to analyse the hydronic control of radiant floor heating systems.